Estudo acústico de tubos de dimensões idênticas e materiais diferentes utilizando bocais de flauta doce e flauta transversal - Piffer, Juliherme Francisco (2011)
Even though scientists have shown so far that the materials used in theconstruction of flutes has little interference in their respective sound characteristics, itseems that there is more to be discussed, because many musicians still insist thatthe material used in the construction of flutes influences significantly the soundproduced. Thus, aiming to search for results that can contribute in this discussion, anacoustic study was carried out with three pairs of tubes of identical dimensions, beingtwo of them made of aluminum, two made of copper and two made of brass. Thepurpose of the study was to compare their respective harmonics sounds in threesimilar experiments: (Experiment 1) tubes coupled to a treble (alto) recordermouthpiece, Yamaha branded, played by a flute player; (Experiment 2) tubes coupledto a transverse flute mouthpiece, in carbon fiber, specially built for this study, playedby another flutist; (Experiment 3) tubes coupled to the same treble (alto) recordermouthpiece, Yamaha branded, played by an artificial blower powered by a cylinder ofnitrogen gas (99.9% of purity) with a controlled and continuous flow. Three audiosignals were captured from each tube in each experiment, on a total of 54 measures.After data selection, in order to exclude parameters, only data with 2 liters/min of flowfrom Experiment 3 (6 measures) was processed and analyzed due to its best quality,best stability and greater accuracy in relation to data obtained in Experiments 1 and2. Thus, it was observed that the fundamental sound and the first two harmonicssounds emitted by each tube were the factors that determined the profile of thesound emitted by the flutes used in this work. From a more detailed analysis of thefrequency distribution adjusted with Lorentzian, it was found that the FWHM (fullwidth at half maximum) of these factors determined the sound characteristic of eachof the metals used. In addition, it was found that, from the realized experiments withfixed parameters (temperature, air humidity, gas flow, gas type, geometry anddimensions of the mouthpieces and tubes), that only type of material was the onlyfactor that determines the profile of the sound produced by the flutes used in thiswork.